Human rights of women : national and international perspectives - Cook, Rebecca J. (Philadelphia : University of Pennsylvania Press, 1994)
How can human rights make a difference in the reality of women's lives? The very notion of human rights implies universal application to both women and men; however, the development of international human rights law has been partial and androcentric, privileging a masculine world view. For most women in the world, reality is long work hours in agriculture or the home, with little or no remuneration, while faced with political and legal processes that ignore their contribution to society and accord little recognition of their particular needs. At the same time, it is a mistake to be limited to a monolithic, essentialized view of women that does not take into account the great differences among women in various regions of the world. For that reason, any attempt to address the human rights of women must consider how they can be protected in the context of their own cultures and traditions. In Human Rights of Women, Rebecca J. Cook and the contributors to this volume seek to analyze how international human rights law applies specifically to women in various cultures worldwide, and to develop strategies to promote equitable application of human rights law at the international, regional, and domestic levels. Their essays present a compelling mixture of reports and case studies from various regions in the world, combined with scholarly assessments of various aspects of international law as these rights specifically apply to women. The book addresses multiple and overlapping agendas: international human rights law, feminist studies, family law, political science, third world studies, jurisprudence, and philosophy. Human Rights of Women gives added inspiration and new opportunities to activists, including but not limited to legal practitioners, who seek practical means by which to make the world fairer for women both inside and outside their homes. A volume in the Pennsylvania Studies in Human Rights.
Foreword / Sonia Picado Sotela -- 1. Women's International Human Rights Law: The Way Forward / Rebecca J. Cook -- 2. To Bellow like a Cow: Women, Ethnicity, and the Discourse of Rights / Radhika Coomaraswamy -- 3. What are "Women's International Human Rights"? / Hilary Charlesworth -- 4. State Responsibility Goes Private: A Feminist Critique of the Public/Private Distinction in International Human Rights Law / Celina Romany -- 5. Intimate Terror: Understanding Domestic Violence as Torture / Rhonda Copelon -- 6. Why Rethinking the Sovereign State is Important for Women's International Human Rights Law / Karen Knop -- 7. State Responsibility Under International Human Rights Law to Change Religious and Customary Laws / Abdullahi Ahmed An-Na'im -- 8. Toward More Effective Enforcement of Women's Human Rights Through the Use of International Human Rights Law and Procedures / Andrew Byrnes -- 9. State Accountability Under the Convention on the Elimination of All Forms of Discrimination Against Women / Rebecca J. Cook -- 10. Toward a More Effective Guarantee of the Enjoyment of Human Rights by Women in the Inter-American System / Cecilia Medina -- 11. Toward a More Effective Guarantee of Women's Rights in the African Human Rights System / Chaloka Beyani -- 12. African Women's Economic, Social, and Cultural Rights -- Toward a Relevant Theory and Practice / Adetoun O. Ilumoka -- 13. Domestic Violence as an International Human Rights Issue / Kenneth Roth -- 14. The Developing Approaches of the International Commission of Jurists to Women's Human Rights / Mona Rishmawi -- 15. General Approaches to Domestic Application of Women's International Human Rights Law / Anne F. Bayefsky -- 16. Obstacles to Women's Rights in India / Kirti Singh -- 17. Challenges to the Application of International Women's Human Rights in the Sudan / Asma Mohamed Abdel Halim -- 18. The Impact of Structural Adjustment Programs on Women's International Human Rights: The Example of Ghana / Akua Kuenyehia -- 19. Canadian Approaches to Equality Rights and Gender Equity in the Courts / Kathleen E. Mahoney -- 20. Equality in the Home: Women's Rights and Personal Laws in South Asia / Sara Hossain -- 21. Using the African Charter on Human and Peoples' Rights to Secure Women's Access to Land in Africa / Florence Butegwa -- 22. Reproductive Rights as Human Rights: The Colombian Case / Maria Isabel Plata -- 23. The Use of International Human Rights Norms to Combat Violence Against Women / Joan Fitzpatrick -- Appendix A. Chart of Ratifications of Selected Human Rights Instruments -- Appendix B. Model Communication Form -- Appendix C. Organizational Resources.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Börngen, ...; Women -- Legal status, laws, etc; Women's rights; Human rights; Feminism; Women's Rights; Human Rights; Feminism; Femmes -- Droit -- Législation.; Femmes -- Droits; Droits de l'homme (Droit international); Féminisme.; feminism; POLITICAL SCIENCE -- Human Rights; Women's rights; Human rights; Feminism; Femmes -- Droit -- Législation.; Femmes -- Droits; Droits de l'homme (Droit international) .; Féminisme.; Mujeres -- Derechos de la mujer; Derechos civiles; Feminismo; Women -- Legal status, laws, etc; Feminism; Human rights; Women -- Legal status, laws, etc; Women's rights; Menschenrecht; Frau; Mensenrechten; Vrouwendiscriminatie; Nationale aspecten; Internationale aspecten; Droits de l'homme (droit international); Femmes -- Statut juridique; Droits de l'homme.; Toronto <1992>